Global value chains and development : redefining the contours of 21st century capitalism - Gereffi, Gary (Cambridge : Cambridge University Press, 2018)
Globalization has transformed how nations, firms and workers compete in the international economy over the past half century. This book by Gary Gereffi, one of the founders of the Global Value Chains (GVC) framework, traces the emergence of arguably the most influential approach used to analyze globalization and its impacts. It studies the conceptual foundations of GVC analysis, the twin pillars of 'governance' and 'upgrading', along with detailed case studies of China, Mexico and other emerging economies as main beneficiaries of export-oriented industrialization, and addresses potential solutions to the deleterious impact of globalization on workers and communities.
Title from publisher's bibliographic system (viewed on 16 Nov 2018).
Keywords: Industries; Labor; Technological innovations -- Economic aspects; Economic development